2010
DOI: 10.5455/pmb.20100427030408
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Chronic Anger and Anger Expression Style in Adolescents with Chronically Illness.

Abstract: AIM: To identify factors associated with trait anger and anger expression style in adolescents with chronic disease. METHODS: The study was included 68 adolescents aged between 10-19 years, who were admitted to the clinic in a university hospital in 2008 after being diagnosed with diabetes, leukemia and chronic kidney failure. As a means of pooling data, “Demographic Questionnaire” and “The State-Trait Anger Scale” were used. RESULTS: Of 68 adolescents participating into the research, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In particular, it has been observed that anger expression, which is one of the patterns of behavior displayed during adolescence, leads to more serious problems when combined with sleeplessness. Studies on anger expression indicate that adolescents have a high level of anger but are generally able to keep this anger under control (Bodur, İnfal, & Kurt, 2010; Wong, Konishi, & Zhao, 2018). Students displaying an aggressive type of behavior have higher anger, anger‐in and anger‐out levels compared with others and the level of their ability to control their anger is lower (Albayrak & Kutlu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been observed that anger expression, which is one of the patterns of behavior displayed during adolescence, leads to more serious problems when combined with sleeplessness. Studies on anger expression indicate that adolescents have a high level of anger but are generally able to keep this anger under control (Bodur, İnfal, & Kurt, 2010; Wong, Konishi, & Zhao, 2018). Students displaying an aggressive type of behavior have higher anger, anger‐in and anger‐out levels compared with others and the level of their ability to control their anger is lower (Albayrak & Kutlu, 2009).…”
Section: Introductionmentioning
confidence: 99%